Exome-wide association study of elite Jamaican and African-American sprint athletes - Tanaka, M.; Fuku, N.; Tanisawa, K.; Higuchi, M.; Miyamoto-Mikami, E.; Wang, G.; Padmanabhan, S.; Cheng, Y.-C.; Mitchell, B. D.; Austin, K.; Pitsiladis, Y. P. (Sport Science Research, 2014)
Elite human athletic performance is a multifactorial trait and previous candidate gene studies have been inconclusive. Purpose: Two exome-wide association studies (EWAS) of elite Jamaican and African-American sprint athletes and respective matched controls were performed to identify common genetic variants. Methods: 95 Jamaican sprint athletes and 102 Jamaican controls, 108 African-American sprint athletes were genotyped using the Illumina® HumanExome BeadChips. Standard EWAS quality control (QC) and population stratification correction were applied to the genotype data. Genetic associations were evaluated by logistic regression/standard allelic association analysis. Meta-analyses were performed for SNPs w ith association P-val ue < 5 x 1 0-5 across the two sprint EWAS sample sets using a fixed-effects model. New significance level was re-defined based on the number of extra meta-analysis tests carried out. Results: After QC, 96,698 autosomal non-synonymous SNPs in 88 Jamaican sprint athletes and 87 Jamaican controls, ca. 153,807 autosomal non-synonymous SNPs in 79 African-American sprint athletes and 391 African-American controls were available for analysis. The genomic inflation factor values were calculated for Jamaican and African-American EWAS sample sets, respectively. Various SNPs showed association with P -val ue < 5 x 10-5 in the respective cohorts. Several SNPs remained significant after meta-analyses. Conclusion: Two putative loci for elite sprint performance across Jamaican and African-American printers have been discovered using an exome-wide association approach followed by meta-analyses. Further validation of these signals requires replication before functional dissection can be carried out.